The Statistical Properties of Spin-One DKP Oscillator under an External Magnetic Field in Noncommutative Space - S. Hassanabadi; M. Ghominejad (Advances in High Energy Physics)
The spin-one Duffin-Kemmer-Petiau oscillator in uniform magnetic field is studied in noncommutative formalism. The corresponding energy is obtained and thereby the corresponding thermal properties are obtained for both commutative and noncommutative cases.